2012
DOI: 10.1002/syn.21582
|View full text |Cite
|
Sign up to set email alerts
|

Subtle biobehavioral effects produced by paternal cocaine exposure

Abstract: Despite the increased prevalence of cocaine use and abuse in males as compared to females, possible effects of paternal cocaine exposure on biobehavioral development has received little attention. We therefore exposed male mice to cocaine (20 mg/kg, i.p.) or vehicle for 10 weeks, and then used those mice as sires. We then behaviorally phenotyped the F1 offspring in order to assess the consequences of paternal cocaine exposure on brain function. We report the presence of a subtle but significant increase in imm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
47
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(51 citation statements)
references
References 50 publications
2
47
1
Order By: Relevance
“…In addition, male F1 offspring of F0 mothers exposed to cocaine prior to pregnancy are more sensitive to the psychomotor effects of cocaine administration (Sasaki et al, 2014). However, contrasting results have been reported for behaviors that may influence drug abuse in offspring derived from paternal cocaine exposure; some have found learning deficits in female F1 offspring of F0 fathers exposed to cocaine (He et al, 2006) while others report no learning effects in either male or female F1 offspring of F0 cocaine-exposed fathers (Killinger et al, 2012). While these results demonstrate some multigenerational effects of cocaine exposure, examination of these phenotypes in the F2 generation will determine transgenerational inheritance.…”
Section: Inheritance Of Drug Exposurementioning
confidence: 92%
“…In addition, male F1 offspring of F0 mothers exposed to cocaine prior to pregnancy are more sensitive to the psychomotor effects of cocaine administration (Sasaki et al, 2014). However, contrasting results have been reported for behaviors that may influence drug abuse in offspring derived from paternal cocaine exposure; some have found learning deficits in female F1 offspring of F0 fathers exposed to cocaine (He et al, 2006) while others report no learning effects in either male or female F1 offspring of F0 cocaine-exposed fathers (Killinger et al, 2012). While these results demonstrate some multigenerational effects of cocaine exposure, examination of these phenotypes in the F2 generation will determine transgenerational inheritance.…”
Section: Inheritance Of Drug Exposurementioning
confidence: 92%
“…Although some evidence indicated that the fertility of cocaine-treated rats was substantially impaired (George et al, 1996), fecundity remained sufficient to examine the effects of paternal cocaine exposure on their offspring. For example, paternal cocaine exposure decreased the weight of their progeny (George et al, 1996; Killinger et al, 2012) but see also (Abel et al, 1989). Experimenter-delivered cocaine to mouse sires also resulted in increased immobility in the tail suspension test, a model of depression, but had no effect on locomotor activity, measures of anxiety or learning and memory (Killinger et al, 2012).…”
Section: Cocainementioning
confidence: 99%
“…For example, paternal cocaine exposure decreased the weight of their progeny (George et al, 1996; Killinger et al, 2012) but see also (Abel et al, 1989). Experimenter-delivered cocaine to mouse sires also resulted in increased immobility in the tail suspension test, a model of depression, but had no effect on locomotor activity, measures of anxiety or learning and memory (Killinger et al, 2012). In contrast, the offspring of mouse sires that self-administered cocaine displayed attention and spatial working memory deficits, particularly among the female progeny (He et al, 2006a).…”
Section: Cocainementioning
confidence: 99%
“…Finally, the drug can produce effects on the mother's physiology that may secondarily influence the fetus, such as increased secretion of stress hormones or altered maternal health behaviors attributable to the mother's addiction. And although it is beyond our scope to review it here, it has recently become clear that paternal exposures, to drugs such as cocaine, during spermatogenesis, can also influence offspring brain development and neurobehavioral development through epigenetic mechanisms, at least in animal models (Killinger et al, 2012;Rodgers et al, 2013;Vassoler et al, 2013). This topic is thus extremely complicated; nevertheless, we will do our best to review both animal models and clinical and imaging data from longitudinal human cohorts following fetal exposure to specific drugs of abuse.…”
Section: Introductionmentioning
confidence: 99%